U-Pb zircon geochronology, geochemistry, and petrogenesis of the Hamech intrusions in the Kuh-e-Shah volcano-plutonic complex, Eastern Iran - Etemadi, A. (2020)
The Hamech area is located in the west of Kuh-e-Shah volcano-plutonic complex, close to the boundary between the Lut Block and Sistan Suture Zone (SSZ), and is composed of monzonite to diorite porphyries and rare gabbro that intruded into older volcanic rocks. U-Pb zircon dating indicates an age of 36.9 ± 1 Ma for gabbro (Late Eocene, Priabonian) and 38.6 ± 0.5 Ma for dacite (Late Eocene, Bartonian). Geochemically, the studied intrusions are dominantly I-type, high-K calc-alkaline, and metaluminous features. Primitive mantle-normalized trace-element spider diagrams of these rocks present enrichment in ion lithophile elements such as Cs, Rb, Ba, K, and Sr and depletion in high field strength elements such as Nb, Ti, Zr, and heavy rare earth elements. Besides, chondrite-normalized rare earth elements plots of the rocks show enrichment in light rare earth elements (6.85 < LaN/YbN < 9.72) and a lack or weak negative Eu anomaly (Eu/Eu* = 0.81–1.02). The initial 87Sr/86Sr and 143Nd/144Nd ratios for the rocks from 0.704541 to 0.704880 and from 0.512633 to 0.512691, respectively, when recalculated to an age of 39 Ma. The εNd(i) values vary from +0.87 to +1.99, which fits into a suprasubduction mantle wedge source for the parental melts. All data suggest that the Hamech intrusions developed in a low maturity continental margin arc setting related to the convergence of the Afghan and Lut Blocks and subduction of Sistan oceanic crust during the Eocene.